Student perceptions on using blogs for reflective learning in higher educational contexts - Irshad Ali; Kevin Byard (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2013)
Increasingly, blogs are being used by educators in higher education for teaching and learning as they have numerous pedagogical benefits. This study describes and analyses the use of blogs as a private journal or e-portfolio for an assessment in a first year bachelor of business programme. Three hundred and fifty students answered an online questionnaire exploring their perceptions of blogs as an assessment tool, in particular ease of use and impact on learning and skills development. Students found numerous benefits of using blogs such as ease of submitting work, increased ownership of learning, and being able to check and improve their work on a regular basis. They also reported that the use of blogs provided flexibility in completing tasks, helped get feedback from lecturers, and increased the quality and quantity of their work. However, there was a lack of consensus on whether blog use improved writing ability of students, increased dialogue between students and lecturers or increased student interest in learning. The challenge for those contemplating using blogs for similar purposes is to ensure that students are provided with sufficient instructions, and constructive, timely feedback.
Keywords: 330; blogs; private journal; higher education